2013
DOI: 10.5455/2319-2003.ijbcp20131218
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amlodipine on blood glucose level and its interaction with oral hypoglycemic drugs in albino rabbits

Abstract: Background: Amlodipine used as many cardiac conditions esp in hypertension. Diabetes affects cardiovascular system adversely. So this study was done to see effect of amlodipine on blood glucose level and its interaction with commonly used oral hypoglycemic agents in diabetic & non diabetic albino rabbits. Methods: Rabbits were divided into nine groups of 6 rabbits in each group. I and II group were non-diabetic given normal saline and amlodipine respectively. Group III to IX were made diabetic by using alloxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…These results are in line with the research conducted by Sandozi (2010), in which the results proved to significantly increase fasting plasma glucose levels of 20 patients was using the CCB antihypertensive group namely amlodipine in the doses of 2.5-10 mg once taken daily for 2-4 weeks. This is also in line with a study carried out by Prajapat, Jain, Singh, Singh, & Agarwal (2013), which stated that amlodipine can significantly increase fasting plasma glucose levels in non-diabetic albino rabbits for 1, 2, and 6 hours after administration of 0.35 mg per kg per day. A study conducted by Sushma et al (2012) gained results of research conducted on albino rabbits which did not suffer from diabetes and the data obtained indicated significantly higher values of the test group were rabbits that had been given amlodipine orally compared to the controlled group which was only given distilled water during the 3 days of treatment, where the results obtained indicated that the mean value of the tested group was significantly higher than the controlled group (p less than 0.001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with the research conducted by Sandozi (2010), in which the results proved to significantly increase fasting plasma glucose levels of 20 patients was using the CCB antihypertensive group namely amlodipine in the doses of 2.5-10 mg once taken daily for 2-4 weeks. This is also in line with a study carried out by Prajapat, Jain, Singh, Singh, & Agarwal (2013), which stated that amlodipine can significantly increase fasting plasma glucose levels in non-diabetic albino rabbits for 1, 2, and 6 hours after administration of 0.35 mg per kg per day. A study conducted by Sushma et al (2012) gained results of research conducted on albino rabbits which did not suffer from diabetes and the data obtained indicated significantly higher values of the test group were rabbits that had been given amlodipine orally compared to the controlled group which was only given distilled water during the 3 days of treatment, where the results obtained indicated that the mean value of the tested group was significantly higher than the controlled group (p less than 0.001).…”
Section: Resultssupporting
confidence: 91%
“…Calcium channel blockers cause hyperglycemia by directly inhibiting insulin secretion. Thus, it is possible that amlodipine, a calcium channel blocker, can affect insulin release, and hence, the occurrence of glucose tolerance may happen to normal and diabetic individuals (Prajapat et al, 2013). According to Medscape (2019), the mechanism of insulin secretion is induced by an increase in plasma glucose levels.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it should be used cautiously in diabetic patients. 18 Similarly, another common interaction (>10%) seen in our study was between metformin and thyroxine. Metformin enhances the effect of thyroxine which is to increases blood glucose.…”
Section: Discussionsupporting
confidence: 59%